2019
DOI: 10.1007/s10643-019-00937-5
|View full text |Cite
|
Sign up to set email alerts
|

Precursor Models and Early Years Science Learning: A Case Study Related to the Water State Changes

Abstract: Children's everyday activities enable them to learn some science even before entering preschool education and children bring these ideas with them when entering education settings. Some of these ideas, or else mental representations, may not be compatible with what is generally accepted by the scientific community. This paper presents the results of an empirical study, focusing on the construction of a precursor model that can support children's scientific learning, in relation to the phenomenon of change of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 23 publications
0
20
0
1
Order By: Relevance
“…The early-year children had been aware about the presence of those simple phenomena of science even though they had not been taught formally by the teacher. Kambouri-Danos et all, [17] reckoned that daily activities of children could help them to easily learn science even before they enter PAUD, and these science knowledges may be developed during the school time. Some appropriate teaching methods may include Inquiry-based learning [18], demonstration [19], experiment [20].…”
Section: Discussionmentioning
confidence: 99%
“…The early-year children had been aware about the presence of those simple phenomena of science even though they had not been taught formally by the teacher. Kambouri-Danos et all, [17] reckoned that daily activities of children could help them to easily learn science even before they enter PAUD, and these science knowledges may be developed during the school time. Some appropriate teaching methods may include Inquiry-based learning [18], demonstration [19], experiment [20].…”
Section: Discussionmentioning
confidence: 99%
“…Kambouri-Danos et al, 2019 [25] Examined the way in which the construction of a precursor model can support children's scientific learning.…”
Section: Structured Interviews Children's Drawingsmentioning
confidence: 99%
“…A small group of studies identified in the current review examined the efficacy of specific teaching interventions/programs, in promoting scientific understanding, within the early childhood setting. Studies identified examined interventions in relation to the development of conceptual understandings of astronomical concepts [20,36], the construction of "pre-cursor" models to support scientific learning [25], the implementation of interventions designed to increase children's voluntary exploration of science centres during free choice play [28] and the combining of a museum and classroom intervention project on science learning in lowincome children [35]. Positive outcomes in relation to the development of science concepts (in children aged 3-6 years) across all the identified studies was noted.…”
Section: Pramling and Pramlingmentioning
confidence: 99%
“…Instead, they are considered as active agents who construct knowledge in the context of social interactions and teaching mediation, based on their previous science-related experiences and conceptions [36,37,[47][48][49]. Under the socio-cognitive lens, knowledge is not seen as objective or independent of the learner, but closely related to the child's life, while knowledge construction, i.e., learning, presupposes her/his action, participation, and active engagement [39,41,48,50].…”
Section: Interpersonal Meaning and Key Socio-cognitive Assumptionsmentioning
confidence: 99%